Pengaruh Intensitas Latihan Beban terhadap Massa Otot - Tambing, Agustina; Engka, Joice N. A.; Wungouw, Herlina I. S. (Universitas Sam Ratulangi, 2020)
Abstract: Muscles can be formed by weight training to be ideal and athletic that will improve performance and confidence of a man. One of the factors that influence weight training is intensity, which shows the severity of the weight of an exercise. The American College of Sports Medicine recommends an intensity of> 70% 1-RM for the purpose of increasing muscle mass. This study was aimed to determine the effect of weight training intensity on muscle mass. This was an experimental study with two group pretest and posttest design. Subjects were 42 Sam Ratuangi University male students divided into two groups. Both groups were given different training intensities (50-60% 1-RM and 50-80% 1-RM). Tricep biceps mass was measured on the circumference of the upper arm using a meter (cm) before and after exercise for 8 weeks. Data were tested for normality using the Shapiro Wilk test and paired t test to determine differences in the average before and after training in each group. In both groups the results showed a p-value of 0.000 (p <0.05), which indicated that there was an increase of muscle mass in each group. Meanwhile, the independent sample t-test of the difference between the two groups obtained a p-value of 0.072 (p> 0.05) which indicated that there was no significant effect between the two different intensities on muscle mass. In conclusion, there was no significant effect of weight training intensity on muscle mass.Keywords: muscle mass, intensity of weight trainingÂ Abstrak: Otot dapat dibentuk dengan latihan beban agar menjadi ideal dan atletis yang akan meningkatkan performa dan kepercayaan diri bagi seorang laki-laki. Salah satu faktor yang memengaruhi latihan beban ialah intensitas, yang menunjukkan berat ringannya beban suatu latihan. American College of Sports Medicine merekomendasikan intensitas>70% 1-RM untuk tujuan peningkatan massa otot. Penelitian ini bertujuan untuk mengetahui pengaruh intensitas latihan beban terhadap massa otot. Jenis penelitian ialah eksperimental dengan rancangan two grouppretest dan posttest. Subjek penelitian ialah mahasiswa Unsrat yang berjenis kelamin laki-laki dengan jumlah 42 orang, dibagi ke dalam dua grup. Kedua grup diberikan intensitas latihan yang berbeda (50-60% 1-RM dan 50-80% 1-RM). Massa otot bisep trisep diukur pada lingkar lengan atas dengan menggunakan meteran (cm) sebelum dan sesudah latihan selama 8 minggu. Data penelitian diuji normalitas dengan Shapiro wilk test dan uji t berpasangan untuk mengetahui perbedaan rerata sebelum dan sesudah latihan pada masing-masing grup. Pada kedua grup didapatkan hasil p=0,000 (p<0,05) yang menunjukkan bahwa terdapat peningkatan massa otot pada setiap grup. Pada uji beda selisih antara kedua grup yang menggunakan independent sample t-test didapatkan nilai p=0,072 (p>0,05) yang menunjukkan tidak terdapat pengaruh bermakna antara kedua intensitas yang berbeda terhadap massa otot. Simpulan penelitian ini ialah tidak terdapat pengaruh bermakna dari intensitas latihan beban terhadap massa otot.Kata kunci: massa otot, intensitas latihan beban